FACTORS OF FORMATION AND IMPROVEMENT OF VOCAL SINGING SKILLS THROUGH FOLKLORE SONGS - Mamarasulzoda Zulxumor Abdulqosimovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract.  This  article  explores  the  factors  influencing  the  development  and enhancement of vocal singing skills through the use of folklore songs. By analyzing the pedagogical, cultural, and technical aspects of folklore singing, the study highlights the role of traditional music in building vocal techniques, emotional expression, and cultural  awareness.  The  findings  underscore  the  pedagogical  value  of  integrating folklore into modern music education.